Cellular diameter in desquamated cells of smokeless tobacco users - Sonia Jaiswal; Pradeep Kumar Sharma; Tahsin Munsif (Asian Journal of Medical Sciences, 2023)
Background: Tobacco-induced mucosal changes have been identified in exfoliated cells. The morphology of the exfoliated cells depends on the nature of the changes taking place in the epithelial layer; conversely, alteration in cytological pattern may be attributed to the changes occurring in the epithelial layer. Applying this possibility, exfoliative cytological techniques have been applied to examine the effect of tobacco on the oral mucosa. Aims and Objectives: The study was conducted to study the alterations in the cellular diameter of buccal mucosal cells. Materials and Methods: In a case controlled study, 240 participants were divided into four groups according to their habit of consumption of tobacco leaves, tobacco with areca nut, participants with oral lesions, and participants without any such habit. The groups were, further, subdivided according to their age. Desquamated cells from the buccal mucosa of were collected and smeared on a slide. The cells were stained with Papanicolou (rapid kit). Fifty cells per slide were studied and photomicrographs were obtained at ×40 magnification. The cellular diameter was obtained using the Leica 1000 software. Results: The mean cell diameter was found to be highest in the group of normal subjects (49.51±7.31 micron), followed by the group of tobacco users (43.52±1.92 micron) and Gutkha users (39.05±3.57 micron). The mean cell diameter was minimum (24.97±3.13 micron) in the group of oral lesion patients. According to the ANOVA test, the difference in cell diameter among various groups is found to be highly significant (P<0.0001). Conclusion: Tobacco used in any form can induce changes in the buccal mucosa. In our study, mean cellular diameter decreased from normal-cells to cells affected by oral lesions.